Laboratory Tests for Subgrade Reaction Coefficient in Seismic Design of Underground Engineering Domain - Kunpeng Xu; Liping Jing; Xinjun Cheng; Haian Liang; Jia Bin (Advances in Civil Engineering)
Subgrade reaction coefficient is commonly considered as the primary challenge in simplified seismic design of underground structures. Carrying out test is the most reliable way to acquire this intrinsic soil property. Owing to the limitations of experimental cost, time consumption, soil deformation mode, size effect, and confined condition, the existing testing methods cannot satisfy the requirements of high-precision subgrade reaction coefficient in seismic design process of underground structures. Accordingly, the present study makes an attempt to provide new laboratory testing methods considering realistic seismic response of soil, based on shaking table test and quasistatic test. Conventional shaking table test for sandy free-field was performed, with the results indicating that the equivalent normal subgrade reaction coefficients derived from the experimental hysteretic curves are reasonable and verifying the deformation mode under seismic excitation. A novel multifunctional quasistatic pushover device was invented, which can simulate the most unfavorable deformation mode of soil during the earthquake. In addition, the first successful application of an innovative quasistatic testing method in evaluating subgrade reaction coefficient was reported. The findings of this study provide preliminary detailed insights into subgrade reaction coefficient evaluation which can benefit seismic design of underground structures.